THE ANTECEDENTS GREEN BRAND EQUITY OF GREEN COSMETICS - Maria Angela Diva (Unib Press Universitas Bengkulu, 2020)
Claim “go-green” continuously used in green marketing to emphasize the attributes of green product and with the aim of developing a green brand. The strength of a green brand reflects in its green brand equity. This study seeks to explore the relationship between green brand equity and its four proposed antecedents, namely the green brand image, green satisfaction, green trust and green brand perceived value. This research used a quantitative approach with self administered survey through an online and offline survey. Data were collected from 303 consumers of green cosmetics. The hypothesis was tested using multiple regression using SPSS 25. The results showed that green brand image, green satisfaction, green trust and green brand perceived value have a positive effect on green brand equity. Hence, investing in resources that increase these antecedents will enhance green brand equity.